Iron oxide nanoparticles effect on growth, physiological traits and nutritional contents of Moringa oleifera grown in saline environment - Tawfik, M. M. (2023)
The obtained results indicate that foliar spraying of Fe3O4NPs significantly promote growth (plant height, branches leaves number per plant, leaf area, stem diameter and biomass). Foliar treatment also increased photosynthetic pigments (chlo.a, chlo b, chlo a/b and carotenoids) and indole acetic acid (IAA) contents comparing with control. Hydrogen peroxide and lipid peroxidation contents of Moringa oleifera leaves were decreased significantly as compared with control plant. The maximum activities of antioxidant enzymes Peroxidase (POX), poly phenol oxidase (PPO), super oxide dismutase (SOD) and nitrate reductase (NR) were observed in plants treated with 40 ppm. Different concentrations of Fe3O4NPs increased significantly crude protein, crude fiber and ash percentages as well as, some nutrient contents of moringa leaves (N, P, K and K/Na) compared with untreated control plants, meanwhile decreased Na contents.